POLICY ON PREVENTION AND HANDLING OF SEXUAL VIOLENCE IN CAMPUS ENVIRONMENT: TREND AND THEMATIC ANALYSIS - Fitriani, Fitriani; Erfina, Erfina; Hardianti, Hardianti (Jurnal Harkat : Media Komunikasi Gender, 2025)
Abstract. Sexual violence in the campus environment is a serious problem that has a wide impact on students, especially women and other vulnerable groups. The Indonesian government has passed the Sexual Violence Crime Law (TPKS Law) as an effort to protect and enforce the law against cases of sexual violence, including in the university environment. This study aims to analyze the effectiveness of the implementation of policies to prevent and handle sexual violence on campus through the Systematic Literature Review (SLR) approach. By examining 500 scientific articles from Dimension, this study evaluates the implementation of the policy and identifies the factors that affect its effectiveness. The results of the study show that although the TPKS Law provides a strong legal basis, its implementation at the campus level still faces challenges such as social stigma, institutional cultural resistance, and limited resources in providing assistance services for victims. Some campuses have adopted reporting mechanisms and protection policies, but there are still gaps in their consistent implementation. This study recommends strengthening more inclusive campus policies, increasing the collective awareness of the academic community, and synergizing with government institutions and civil society organizations in dealing with sexual violence more comprehensively. The results of this research are expected to contribute to the development of more effective policies to create a safe and free academic environment from sexual violence. Abstrak. Kekerasan seksual di lingkungan kampus menjadi permasalahan serius yang berdampak luas terhadap mahasiswa, terutama perempuan dan kelompok rentan lainnya. Pemerintah Indonesia telah mengesahkan Undang-Undang Tindak Pidana Kekerasan Seksual (UU TPKS) sebagai upaya perlindungan dan penegakan hukum terhadap kasus-kasus kekerasan seksual, termasuk di lingkungan perguruan tinggi. Penelitian ini bertujuan untuk menganalisis efektivitas implementasi kebijakan pencegahan dan penanganan kekerasan seksual di kampus melalui pendekatan Systematic Literature Review (SLR). Dengan menelaah 500 artikel ilmiah dari Dimension, penelitian ini mengevaluasi implementasi kebijakan serta mengidentifikasi faktor-faktor yang mempengaruhi efektivitasnya. Hasil penelitian menunjukkan bahwa meskipun UU TPKS memberikan dasar hukum yang kuat, implementasi di tingkat kampus masih menghadapi tantangan seperti stigma sosial, resistensi budaya institusional, serta keterbatasan sumber daya dalam menyediakan layanan pendampingan bagi korban. Beberapa kampus telah mengadopsi mekanisme pelaporan dan kebijakan perlindungan, namun masih terdapat kesenjangan dalam penerapannya secara konsisten. Penelitian ini merekomendasikan penguatan kebijakan kampus yang lebih inklusif, peningkatan kesadaran kolektif civitas akademika, serta sinergi dengan lembaga pemerintah dan organisasi masyarakat sipil dalam menangani kekerasan seksual secara lebih komprehensif. Hasil penelitian ini diharapkan dapat berkontribusi pada pengembangan kebijakan yang lebih efektif guna menciptakan lingkungan akademik yang aman dan bebas dari kekerasan seksual.